Identification of Sensitive Predictors of Levator Ani Tear during First Complex Vaginal Birth. (4th October 2013) - Low, Lisa Kane; Zielinski, Ruth; Tao, Yebin; Brandon, Catherine; Miller, Janis
<x xml:space="preserve">Abstract</x> Objective To determine maternal characteristics and birth events most predictive of increasing severity of levator ani tears, a recognized predisposing factor to pelvic floor disorders later in a woman's lifespan, so that prevention strategies may be developed. Significance Several studies link vaginal birth with levator ani tears resulting in increased risk of developing pelvic floor disorders later in life. The events of vaginal birth that contribute to development of levator ani tears and how these factors are linked are not explicitly known. Prior retrospective investigations indicated age greater than 33 years, use of forceps or vacuum, more than 150 minutes in second stage, anal sphincter tear, or macrosomic infant greater than 4000 grams were risk factors for levator ani tears. Taken together, we refer to women who had at least one of these factors as having a "complex" birth. Methods We purposefully recruited and enrolled primiparous women immediately postpartum who experienced a complex vaginal birth. Participants were evaluated with magnetic resonance imaging (MRI) 2 months postpartum. Severity level of levator ani tears was graded by degree of muscle volume loss measured on an ordinal scale as: 0) none, 1) less than 50% loss unilateral, 2) greater than or equal to 50% unilateral or less than 50% bilateral, and 3) greater than or equal to 50% bilateral. During analysis additional risk factors considered included episiotomy, infant head circumference, duration of active pushing, and use of epidural and oxytocin. Ordinal logistic regression was used for analysis with significance at P < .05 for univariate predictors. Findings Ninety women successfully completed the MRI and the majority (64.4%) showed no visible levator ani muscle loss, 10% showed only minor muscle volume loss, with 25.8% in severe muscle loss categories. Significant predictors of tear severity were time spent in active pushing (P = 0.04), not total time in second stage, and age (P = 0.02). Use of episiotomy was not statistically significant (P = 0.05). Discussion Despite recruiting women who experienced a complex birth, only about a quarter actually had clinically relevant levator ani tears. In this investigation of at‐risk women, significant predictors of levator ani tear severity included increasing age and duration of active pushing. When considering prevention, age is not modifiable, but monitoring active pushing time and potentially avoiding episiotomy warrant further investigation. Funding NIH Funding R21HD049818 and P50HD044406 002.